POUR UNE APPROCHE LUDIQUE EN CLASSE DE LANGUE : ACTIVITÉS ET ADAPTATIONS POUR LA CLASSE DE 5AP EN ALGÉRIE - Boulanouar Yousfi (Studii de gramatică contrastivă)
The supports and strategies that allow the development of communication skills in language classes are multiple. We can cite, as an example, exercises and activities, practices characterized by an obvious diversity and richness. The fun activities, which we propose to study in this article, represent one of the types of exercises listed by the didacticians. These are activities that could be useful for learners whose goal is to motivate them, make them work and develop their communication, linguistic and cultural skills. Our objective is to show how these supports can be used in class within the framework of official programs and school textbooks intended for the 5th year of primary school in Algeria.